2020
DOI: 10.3390/md18060321
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Terpenes from Marine-Derived Fungi: 2015–2019

Abstract: Marine-derived fungi are a significant source of pharmacologically active metabolites with interesting structural properties, especially terpenoids with biological and chemical diversity. In the past five years, there has been a tremendous increase in the rate of new terpenoids from marine-derived fungi being discovered. In this updated review, we examine the chemical structures and bioactive properties of new terpenes from marine-derived fungi, and the biodiversity of these fungi from 2015 to 2019. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 153 publications
0
48
0
5
Order By: Relevance
“…The 1 H NMR spectrum ( Figure S2) (Table 1) along with the HSQC experiment showed three aromatic protons owing to a 1,2,3-trisubstituted aromatic ring [δ H 7.56 (1H, t, J = 7.9 Hz); 6.96 (1H, dd, J = 2.5, 7.3 Hz); 6.96 (1H, dd, J = 2.5, 7.3 Hz)], three methines [δ H 5.90 (1H ,t, J = 6.6 Hz); 4.86 (1H, m); 3.73 (1H, m);], one methylene [δ H 2.95 (2H, m)], and two methyls [1.25 (3H, d, J = 6.4 Hz); 1.18 (3H, d, J = 6.4 Hz)]. The 13 C NMR ( Figure S3) and HSQC data ( Figure S4) of 1 indicated the presence of 14 carbons for eight sp 2 hybridized carbons including two ester carbonyls (δ C 171.5, 168.8) and six sp 3 A 7-hydroxybenzofuran was assigned by 1 H-1 H COSY correlations ( Figure S5) between H-4 and H-5, H-5 and H-6, H-6 and H-7, and HMBC correlations ( Figure S6) from H-4 to C-3a and C-7a, and H-3 to ester carbonyl C-1, as well as four-bond W-type correlation from H-6 to ester carbonyl C-1 ( Figure 2). The HMBC correlations from H-8 to C-3 and H-3 to C-9 indicated that C-8 of acetoxy was linked to C-3 of 7-hydroxy-benzofuran group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H NMR spectrum ( Figure S2) (Table 1) along with the HSQC experiment showed three aromatic protons owing to a 1,2,3-trisubstituted aromatic ring [δ H 7.56 (1H, t, J = 7.9 Hz); 6.96 (1H, dd, J = 2.5, 7.3 Hz); 6.96 (1H, dd, J = 2.5, 7.3 Hz)], three methines [δ H 5.90 (1H ,t, J = 6.6 Hz); 4.86 (1H, m); 3.73 (1H, m);], one methylene [δ H 2.95 (2H, m)], and two methyls [1.25 (3H, d, J = 6.4 Hz); 1.18 (3H, d, J = 6.4 Hz)]. The 13 C NMR ( Figure S3) and HSQC data ( Figure S4) of 1 indicated the presence of 14 carbons for eight sp 2 hybridized carbons including two ester carbonyls (δ C 171.5, 168.8) and six sp 3 A 7-hydroxybenzofuran was assigned by 1 H-1 H COSY correlations ( Figure S5) between H-4 and H-5, H-5 and H-6, H-6 and H-7, and HMBC correlations ( Figure S6) from H-4 to C-3a and C-7a, and H-3 to ester carbonyl C-1, as well as four-bond W-type correlation from H-6 to ester carbonyl C-1 ( Figure 2). The HMBC correlations from H-8 to C-3 and H-3 to C-9 indicated that C-8 of acetoxy was linked to C-3 of 7-hydroxy-benzofuran group.…”
Section: Resultsmentioning
confidence: 99%
“…Marine-derived fungi are a significant source of pharmacological molecules with interesting and diversified structural properties [1][2][3][4]. Among them, the fungal genus Alternaria had a widespread distribution in marine source [4] (including sediment [5], sponge [6], alga [7], mangrove [8], soft coral [9]) and could produce plenty of structural molecules, including nitrogen-containing compounds, steroids, terpenoids, pyranones, quinones, and phenolics [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to bacteriocins, a wide variety of novel gene clusters encoding putative terpenes, NRPs, polyketides, and other active compounds have been uncovered by in silico analysis, creating new opportunities for drug development [23,24,49,79]. NRPs and terpenes have been reported with activity against several antibiotic-resistant strains [80][81][82][83][84][85]. A small library of predicted NRP peptides was chemically synthesized, based on the primary sequence of NRP clusters in the human microbiome, and a potent anti-MRSA (methicillin-resistant Staphylococcus aureus) peptide with a new mechanism of action, named humimycin, was identified [80].…”
Section: Discussionmentioning
confidence: 99%
“…are reported to produce many terpenes, their responsible biosynthetic gene clusters in Trichoderma have been under-investigated. 53,82,103,104 T. viride J1-030 was mined for terpene cyclases, one of which, named Tvi09626, was expressed in an FPP-overproducing strain of S. cerevisiae. This produced a new 5/6 bicyclic brasilane-type sesquiterpene 72 (Scheme 5).…”
Section: Trichobrasilenolmentioning
confidence: 99%